Application of 3D-print silica bolus for nasal NK/T-cell lymphoma radiation therapy. (22nd September 2020) - Dai, Guyu; Xu, Xin; Wu, Xiaohong; Lei, Xiaolin; Wei, Xing; Li, Zhibin; Xiao, Qing; Zhong, Renming; Bai, Sen
Abstract: The aim of the study was to evaluate the clinical feasibility of a 3D-print silica bolus for nasal NK/T-cell lymphoma radiation therapy. Intensity modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) plans were designed using an anthropomorphic head phantom with a 3D-print silica bolus and other kinds of bolus used clinically, and the surface dose was measured by a metal oxide semiconductor field-effect transistor (MOSFET) dosimeter. Four nasal NK/T patients with or without 3D-print silica bolus were treated and the nose surface dose was measured using a MOSFET dosimeter during the first treatment. Plans for the anthropomorphic head phantom with 3D-print bolus have more uniform dose and higher conformity of the planning target volume (PTV) compared to other boluses; the homogeneity index (HI) and conformity index (CI) of the VMAT plan were 0.0589 and 0.7022, respectively, and the HI and CI of the IMRT plan were 0.0550 and 0.7324, respectively. The MOSFET measurement results showed that the surface dose of the phantom with 3D-print bolus was >180 cGy, and that of patients with 3D-print bolus was higher than patients without bolus. The air gap volume between the 3D-print bolus and the surface of patients was <0.3 cc. The 3D-print silica bolus fitted well on the patient's skin, effectively reducing air gaps between bolus and patient surface. Meanwhile, the 3D-print silica bolus provided patients with higher individuation, and improved the conformity and uniformity of the PTV compared to other kinds of boluses.